Investigating the high yield extraction of pectin from Crissampelos Pareira L. Vat. Hirsute planted in Vietnam (International Journal of Scientific Research and Management (IJSRM), 2022)
The study on the most suitable extracting conditions of pectin from Crissampelos pareira L. Var. Hirsute was thoroughly and successfully investigated. It was found that the most suitable conditions for the extraction of pectin from C pareira were at temperature of 90°C; pH of solution of 1.5; and the extraction time of 60 minutes. The average yield of pectin was of 15.58%. it is worth noting that the mentioned extracting conditions showed a highly significant effect (p<0.05) on the yield of pectin. As the consequence, the equivalent weight, methoxyl content, anhydrouronic acid content, degree of esterification and moisture content of extracted pectin obtained under the suitable conditions were found to be 333.33 g/mol, 5.58%, 84.48%, 37.5%, 15.76%, respectively.